How to Include Patients' Perspectives in the Study of the Mind: A Review of Studies on Depression - Löffler-Stastka, Henriette; Bednar, Kathrin; Pleschberger, Ingrid; Prevendar, Tamara; Pietrabissa, Giada (Frontiers in Psychology, 2021)
Depression has been widely studied by researchers from different fields, but its causes, and mechanism of action are still not clear. A difficulty emerges from the shifting from objective diagnosis or analysis to exploration of subjective feelings and experiences that influence the individuals’ expression, communication and coping in facing depression. The integration of the experiential dimension of the first-person in studies on depression - and related methodological recommendations - are needed to improve the validity and generalizability of research findings. It will allow the development of timely and effective actions of care. Starting from providing a summary of the literature on theoretical assumptions and considerations for the study of the mind, with particular attention to the experiential dimension of patients with depression (aim #1 and #2), this contribution is aimed to provide practical suggestions for the design of research able to incorporate first- and third-person accounts (aim #3). It is also aimed to review qualified phenomenological methods for the acquisition and interpretation of experiential data in patients with depression (aim #4). Recognizing the first-person perspective in the study of depression is a major step towards a better understanding and treatment of this disorder. Theoretical constructs and technique suggestions that result from this review offer a valid starting point for the inclusion of the experiential dimension to common third-person research in the study of the mind.